Visualizing the Financial Impact of Presidential Tweets on Stock Markets - Ujwal Kandi, Sasikanth Gujjula, Venkatesh Buddha, V S Bhagavan (International Journal of Advanced Science and Technology, 2020)
As more and more data being created every day, all of it can help take better decisions with data analysis. It is not different with data generated in financial markets. Here we examine the process of how global economy is affected by the market sentiment influenced by the micro-blogging data (tweets) of the American President Donald Trump. The news feed is gathered from The Guardian and Bloomberg from the period between December 2016 and October 2019, which are used to further identify the potential tweets that influenced the markets as measured by changes in equity indices. Keywords: Stock Market Performance, Stock Price, President Trump, Tweets, Behavioral Finance.